Nanoscale Advances in Catalysis and Energy Applications - Li, Yimin; Somorjai, Gabor A (Nano letters, 2010)
In this perspective, we present an overview of nanoscience applications in catalysis, energy conversion, and energy conservation technologies. We discuss how novel physical and chemical properties of nanomaterials can be applied and engineered to meet the advanced material requirements in the new generation of chemical and energy conversion devices. We highlight some of the latest advances in these nanotechnologies and provide an outlook at the major challenges for further developments.